2009
DOI: 10.1182/blood-2007-10-121426
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring of FLT3 in the endoplasmic reticulum alters signaling quality

Abstract: The mechanism of cell transformation by Fms-like tyrosine kinase 3 (FLT3) in acute myeloid leukemia (AML) is incompletely understood. The most prevalent activated mutant FLT3 ITD exhibits an altered signaling quality, including strong activation of the STAT5 transcription factor. FLT3 ITD has also been found partially retained as a high-mannose precursor in an intracellular compartment. To analyze the role of intracellular retention of FLT3 for transformation, we have generated FLT3 versions that are anchored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
100
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 34 publications
11
100
0
Order By: Relevance
“…Yet another factor that could contribute to the differences in phosphorylation sites seen in these experiments is the subcellular localization of the receptor. It is known that the FLT3-ITD, in contrast to wild-type FLT3 and FLT3-D835Y is trapped in the endoplasmic reticulum and does not reach the cell surface to any appreaciable extent [47]. Thus, the signal transduction molecules (including kinases and phosphatases) it encounters is likely to be different from those at the cell surface, and this could contribute to the differences in phosphorylation seen in the different forms of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another factor that could contribute to the differences in phosphorylation sites seen in these experiments is the subcellular localization of the receptor. It is known that the FLT3-ITD, in contrast to wild-type FLT3 and FLT3-D835Y is trapped in the endoplasmic reticulum and does not reach the cell surface to any appreaciable extent [47]. Thus, the signal transduction molecules (including kinases and phosphatases) it encounters is likely to be different from those at the cell surface, and this could contribute to the differences in phosphorylation seen in the different forms of the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, arguing against this scenario are studies that express ITD and AL mutations in the same cell type and yet more aggressive transforming properties are observed for the ITD mutant Grundler et al, 2005). Clear differences in activation of downstream signaling pathways Schmidt-Arras et al, 2009) and in transcription profiles Lu et al, 2007) between the two classes of mutations have been reported. A switch in substrate specificity can account for these observations.…”
Section: Differences In Oncogenic Flt3 Signalingmentioning
confidence: 99%
“…Constitutive activity of FLT3-ITD activates down-stream pro-survival signaling pathways including PI3K/AKT, STAT5 (whereby STAT5 activation is independent of JAK kinase activation [49]) and RAF/MEK/ERK, which are known to promote survival, proliferation and transformation [50][51][52]. Recent findings have identified that in order for PI3K/AKT and RAF/MEK/ERK pro-survival pathways to be activated they must be located down-stream of FLT3-ITD at the plasma membrane and STAT5 is located down-stream of FLT3-ITD at the ER [45,53].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%